Biomechanical analysis of posterior lumbar interbody aages - Lekthumi, Amutha; Mazlan, Muhammad Hazli; Ahmad, Ida Laila; Abdullah, Abdul Halim; Abd Jalil, Muhammad Hilmi (Penerbit UTHM, 2020)
A popular yet effective surgical treatment used in medical field to treat degenerative disc disease related to low back pain is known as the lumbar interbody fusion procedure. One of the main aims of posterior lumbar interbody fusion (PLIF), using cages or bone grafts are to provide stability during body movements and mechanical support between two vertebrae, maintain disc height and to help out with the fusion process. This procedure restores disc height, enlarges the stenotic foramen, stabilises the spine, and provides mechanical strength between vertebrae.